Kajian Pengendalian Tingkat Bahaya Erosi dari Perspektif Sosial Budaya di Daerah Aliran Sungai (DAS) Ekat Tono - Aris Onisinus Tamonob; Ludji Michael Riwu Kaho; Normal P. L. B. Riwu Kaho (Wana Lestari, 2024)
Erosion is an event where the surface soil layer is eroded by various things, especially rainwater, and is an environmental problem that cannot be ignored because it has a bad and big impact on various sectors of living creatures, especially humans. For this reason, it is necessary to carry out preventive controls through good land management procedures. This research was conducted to see the magnitude of erosion from each form of land control (processing) such as in forest areas, mammals, and open fields or gardens implemented by the Inbate Village Community from a socio-cultural view or perspective. The results of the research show the severity class and magnitude of erosion values ​​from the three locations, namely the heavy erosion hazard class is found in the open field/garden area with an erosion magnitude of 212.21 tonnes/ha/year, while the mamar area is classified as a light erosion hazard class with a magnitude erosion was 30.32 tonnes/ha/year and the forest area was classified as very light erosion hazard class with an erosion magnitude of 3.32 tonnes/ha/year.